Developing reflection and critical thinking in a leadership education course: leading learning and change. Issue 12 (2nd December 2022) - Wheeley, Elizabeth; Klieve, Helen; Clark, Lorna
ABSTRACT: In higher education learning environments, critical thinking is often an assumed skill; however, many students require explicit support to effectively achieve in this area. This research focuses on the application of scaffolded learning experiences to promote reflection and critical thinking in a post-graduate educational leadership course. It particularly recognises the unique challenges for international students, managing their transition into a culturally different learning environment while meeting the academic and critical thinking demands of higher education. This research draws on two main data sources: student survey responses regarding reflections on the concept of leadership and researcher reflections on student engagement and critical thinking. Descriptive analysis provided profiles of the student cohort and their views on leadership. Three themes emerged from the analysis of open-ended responses regarding views on leadership: diverse understandings of leadership; the importance of leadership actions for change; and evaluating leadership – self and others. Reflections from one researcher on the conduct of the course and student work provided a link between the initial design and student outcomes. Two levels of positive outcomes were found. Firstly, a greater level of early engagement in course learning activities was observed which continued across the course. Secondly, students' learning and achievement were greater than a previous cohort implying the benefits of early modelling of reflective practices to scaffold students' critical thinking. Importantly, stronger tutorial engagement supporting critical reflections is likely to translate to other post-graduate studies. Recommendations for further research on students' engagement and critical thinking are proposed.